Ukraine in the Face of Economic and Political Challenges - Rubaj, Piotr; Voytsekhovska, Viktoriya (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article presents the current economic and social situation of Ukraine and the possible scenarios for its future development. It seems that deep structural reforms, rapprochement with EU and ending the conflict in the Donbas are essential to improving Ukraine’s standard of living and sense of security. These processes are very complicated and render significant progress in the near term unlikely. The crisis in Ukraine has an important impact on neighbouring Poland, for which this publication reviews the potential economic and social implications.